Characterization of The Volcanic Rocks of Mount Sinabung, Simacem Village, Karo Regency, Conducted With XRD, SEM-EDX - Sinuhaji, Perdinan (Journal of Technomaterial Physics, 2019)
The study of volcanic rocks characterization of Sinabung Volcano erupted on September 15, 2017. The volcanic rocks crystal system was performed with XRD, elemental analysis and microstructure with SEM-EDX. Volcanic rocks contain: Anorthite phase 87,11 (wt%), Triclinic crystal, lattice constant, a = 8.1742 Å, b = 12,844 Å, c = 14,204 Å; Quartz phase 2.26%, Hexagonal crystals, lattice constants, a = 4,799 Å, b = 4,799 Å, c = 5,379 Å; Cristobalite phase 7.72 (wt%), Tetragonal crystals, lattice constants a = 4,970 Å, b = 6,990 Å, c = 6,998 Å; Alunite phase 2.91 (wt%), Hexagonal crystals, lattice constants, a = 6,990 Å, b = 6,990 Å, c = 17,282 Å.